Damage resistance of CSA-doped PANI/epoxy CFRP composite during passing the artificial lightning through the aircraft rivet. (December 2017) - Katunin, Andrzej; Sul, Przemysław; Łasica, Andrzej; Dragan, Krzysztof; Krukiewicz, Katarzyna; Turczyn, Roman
Abstract: Lightning strike protection (LSP) of aircraft polymer-based composite structures is one of key structural problems in aircraft industry. Among various currently developed LSP solutions, which based on impregnation of metallic meshes, dispersion of metallic particles or carbon nanostructures, the currently developed solution is based on the intrinsically conductive polymer (polyaniline doped with camphorsulfonic acid), which allows for increasing its electrical conductivity, and retaining its low mass and high mechanical strength as well as simple and inexpensive manufacturing in comparison to other LSP solutions. In this study, the damage resistance of the developed composite to artificial lightning currents passing through aluminium rivets placed in a composite structure is investigated by means of X-ray computed tomography. The comparative studies of a classical CFRP structure and the developed electrically conductive CFRP structure is performed in order to highlight the advantage of the developed composite material. The obtained results show high resistance of the developed material to the high-current lightning-type discharges through the metallic rivets, which make it a promising material for aircraft structural applications. Highlights: The new conductive composite were introduced for lightning strike protection. The resistance to lightning-type strikes through the metallic rivet is tested. The developed composite is characterized by higher resistance in comparison to CFRP.